Clinical presentation, ICU management and outcome in severe COVID-19 disease - A prospective observational study - Prakash Shastri (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2023)
Aim: We conducted a prospective, observational study to describe the clinical characteristics, management, and outcomes of patients with moderate to severe coronavirus disease admitted to the Intensive Care Unit (ICU). Methods: The study was conducted from 1st July 2020 to 31st December 2020. The criteria for ICU admission included a positive Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) for the novel Coronavirus (SARS-CoV-2) and oxygen saturation of less than 90% with or without oxygen. Results: A total of 621 patients were included (median age, 59 years [interquartile range IQR, 48-68]; 75.8% were males. The common comorbidities were hypertension (323 [52%]), and diabetes mellitus. 96 (15.5%) patients underwent mechanical ventilation, 18 (2.9%) received renal replacement therapy, and 223 (36%) died. The median age in non-survivors was significantly higher [63 years (IQR 55-71)] vs. 57 years (IQR 46-66)] (p < 0.001). Hypoxia (oxygen saturation (SpO2 < 90%) and shortness of breath suggestive of impending respiratory failure were the most common symptoms necessitating ICU admission. A low absolute lymphocyte count (ALC), and high levels of inflammatory biomarkers which persisted for seven days after diagnosis were significantly associated with non-survival. Multivariate logistic regression analysis showed shortness of breath (SOB), hypoxia (SpO2 < 90% on oxygen), use of neuromuscular blockers, and chronic kidney disease as independent risk factors associated with mortality as were the severity scores (APACHE and SOFA). Conclusion: This single-center case series provides clinical characteristics and outcomes of patients with confirmed COVID-19 disease admitted to the COVID ICU. These findings are important for guiding research and preparing for future pandemics.